3D printed fracture reduction guides planned and printed at the point of care show high accuracy – a porcine feasibility study - Andreas Hecker; Sophie C. Eberlein; Frank M. Klenke (Journal of Experimental Orthopaedics)
Abstract Purpose After surgical treatment of comminuted diaphyseal femoral and tibial fractures, relevant malalignment, especially rotational errors occur in up to 40–50%. This either results in a poor clinical outcome or requires revision surgery. This study aims to evaluate the accuracy of reduction if surgery is supported by 3D guides planned and printed at the point of care. Methods Ten porcine legs underwent computed tomography (CT) and 3D models of femur and tibia were built. Reduction guides were virtually constructed and fitted to the proximal and distal metaphysis. The guides were 3D printed using medically approved resin. Femoral and tibial comminuted diaphyseal fractures were simulated and subsequently reduced using the 3D guides. Postoperative 3D bone models were reconstructed to compare the accuracy to the preoperative planning. Results Femoral reduction showed a mean deviation ± SD from the plan of 1.0 mm ± 0.9 mm for length, 0.9° ± 0.7° for varus/valgus, 1.2° ± 0.9° for procurvatum/recurvatum and 2.0° ± 1.7° for rotation. Analysis of the tibial reduction revealed a mean deviation ± SD of 2.4 mm ± 1.6 mm for length, 1.0° ± 0.6° for varus/valgus, 1.3° ± 1.4° for procurvatum/recurvatum and 2.9° ± 2.2° for rotation. Conclusions This study shows high accuracy of reduction with 3D guides planned and printed at the point of care. Applied to a clinical setting, this technique has the potential to avoid malreduction and consecutive revision surgery in comminuted diaphyseal fractures. Level of Evidence Basic Science.